The man who would be king [videorecording (DVD)] - Huston, John, 1906-1987; Connery, Sean; Caine, Michael; Plummer, Christopher; Kipling, Rudyard, 1865-1936 (Warner Brothers Entertainment, 2010)
Based on a Rudyard Kipling story and packed with spectacle, humor, excitement and bold twists of fate, John Huston's film of The Man Who Would be King earns its crown as "an epic like no other. One of the screen's great adventure yarns" (Danny Peary, Guide for the Film Fanatic). Sean Connery and Michael Caine -- chins out, shoulders squared and with a sly wink -- star as British Sargeants Danny Dravot and Peachy Carnehan. The Empire was built by men like these two. Now they're out to build their own empire, venturing into remote Kafiristan to become rich as kings-- Container.